Model Manajemen Pendidikan Berbasisi Adab - Gani, Syarif Hidayatullah; Mujahidin, Endin; Sa'diyah, Maemunah (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Instilling adab is the most important thing for a teacher to students, because students are a mandate entrusted by Allah to be nurtured, guided, and educated carefully so that later they become useful human beings. The purpose of this research is to find out how the process of managing adab education occurs at MTs Al - Ahsan, Bogor City. The research methodology is a qualitative research method with a descriptive approach. The findings from the research show that the adab education management process is implemented by routinely reading Al-Qur'an Juz 30, praying dhuha in congregation, then continuing with listening to tausiyah and studying the book